Survival of reproductive behaviors in estrogen receptor β gene-deficient (βERKO) male and female mice - Ogawa, Sonoko (The National Academy of Sciences, 1999)
Previously, it was shown that the lack of a functional estrogen receptor (ER) α gene (ERα) greatly affects reproduction-related behaviors in both female and male mice. However, widespread expression of a novel second ER gene, ERβ, demanded that we examine the possible participation of ERβ in regulation of these behaviors. In dramatic contrast to our results with ERα knockout (αERKO) males, βERKO males performed at least as well as wild-type controls in sexual behavior tests. Moreover, not only did βERKO males exhibit normal male-typical aggressive behavior, including offensive attacks, but they also showed higher levels of aggression than wild-type mice under certain conditions of social experience. These data revealed a significant interaction between genotype and social experience with respect to aggressive behavior. Finally, females lacking a functional β isoform of the ER gene showed normal lordosis and courtship behaviors, extending in some cases beyond the day of behavioral estrus. These results highlight the importance of ERα for the normal expression of natural reproductive behaviors in both sexes and also provide a background for future studies evaluating ERβ gene contributions to other, nonreproductive behaviors.